Does generation Z interest in participating webinar post covid-19 pandemic? Study using the UTAUT model approach: English - Fikri Haykal Sodiq (International Journal of Economics, Business and Innovation Research, 2024)
Webinars are a technology that allows users to hold seminars, talk shows, discussions and other activities carried out online or using the internet without having to meet face to face. The aim of this research is to determine the influence of performance expectations, business expectations, social influences, and facilitating conditions on students' interest in using webinars based on the Unified Theory of Acceptance and Use of Technology (UTAUT) model. This research uses quantitative methods with data collected and distributed via Google Form and processed using IBM SPSS Statistics 29 software. The results of this research show that business expectations and facilitating conditions have a significant effect on students' interest in using webinars. Meanwhile, performance expectations and social influence do not significantly influence students' interest in using webinars.